Análise da interação entre os modos de flambagem local e distorcional em perfis de aço formados a frio com seção rack sob compressão axial - Campos, Raquel Gabriela Alves (2020)
In the last decade, several researches were developed to investigate the localdistortional buckling interaction (LD) of thin-walled steel columns with lipped channel cold-formed section (CFS). However, extending the findings to columns displaying other cross-sectional shapes it is essential to assess the generality of the proposed solutions, thereby paving the way for the application of the Direct Strength Method (DSM) design approach for columns with other cross-section shapes affected by LD interaction. Therefore, this research aims to investigate the interaction behavior between local and distortional buckling modes of cold-formed steel columns with rack section, without holes. The study will be based on (i) the experimental results published by previous investigations, (ii) the development of an appropriate shell finite element numerical model using the computation program ANSYS and (iii) the adoption of the principles of the Direct Strength Method (DSM). It is expected that the combination of the cited structural analysis resources allows improving design procedures of CFS rack column members. The application of an existing formulation in the literature to predict localdistortional interaction has led to appropriate and accurate results.